2012
DOI: 10.1038/ajh.2011.210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Sodium Diet vs. High-Sodium Diet on Blood Pressure, Renin, Aldosterone, Catecholamines, Cholesterol, and Triglyceride (Cochrane Review)

Abstract: Sodium reduction resulted in a significant decrease in BP of 1% (normotensives), 3.5% (hypertensives), and a significant increase in plasma renin, plasma aldosterone, plasma adrenaline, and plasma noradrenaline, a 2.5% increase in cholesterol, and a 7% increase in triglyceride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1
22

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(201 citation statements)
references
References 169 publications
9
162
1
22
Order By: Relevance
“…5 g per day contributes to lowering BP by 4-5 mm Hg in hypertensive persons and about 1-2 mm Hg in normotensive persons [19]. In a landmark study, the International Study of Salt and Blood Pressure (INTERSALT) international research project involving more than 10,000 people aged 20-59 from 32 countries -it was demonstrated that the difference in sodium intake of 100 mmol per day (6 g NaCl) is associated with the difference of SBP/ /DBP of 6/3 mm Hg [20].…”
Section: Discussionmentioning
confidence: 99%
“…5 g per day contributes to lowering BP by 4-5 mm Hg in hypertensive persons and about 1-2 mm Hg in normotensive persons [19]. In a landmark study, the International Study of Salt and Blood Pressure (INTERSALT) international research project involving more than 10,000 people aged 20-59 from 32 countries -it was demonstrated that the difference in sodium intake of 100 mmol per day (6 g NaCl) is associated with the difference of SBP/ /DBP of 6/3 mm Hg [20].…”
Section: Discussionmentioning
confidence: 99%
“…III) BP obejmują zwiększenie objętości zewnątrzkomórkowej oraz wzrost obwodowego oporu naczyniowego, częściowo z powodu aktywacji układu współczulnego [343]. Zwykłe spożycie soli w wielu krajach wynosi 9-12 g dziennie i wykazano, że jego zmniejszenie do ok. 5 g dziennie powoduje niewielkie (o 1-2 mm Hg) obniżenie SBP u osób normotensyjnych, natomiast wywiera nieco większy efekt (obniżenie SBP o 4-5 mm Hg) u osób z nadciśnieniem [339,344,345]. W populacji ogólnej zaleca się więc spożycie 5-6 g soli dziennie.…”
Section: S 61unclassified
“…W populacji ogólnej zaleca się więc spożycie 5-6 g soli dziennie. Efekt ograniczenia spożycia sodu jest większy u osób rasy czarnej, osób starszych, a także u pacjentów z cukrzycą, zespołem metabolicznym lub CKD, a ograniczenie spożycia soli umożliwia redukcję liczby i dawek leków hipotensyjnych [345,346]. Wpływ zmniejszenia spożycia soli na występowanie incydentów sercowo-naczyniowych pozostaje niejasny [347][348][349][350], chociaż w długoterminowej obserwacji w badaniu Trials of Hypertension Prevention (TOHP) wykazano, że obniżenie spożycia soli wiązało się z mniejszym ryzykiem incydentów sercowo-naczyniowych [351].…”
Section: S 61unclassified
“…Navedena studija, kao i još nekoliko kontroverznih studija i komentara (109,110,111) inicirale su SZO da sačini globalne, na nauci zasnovane preporuke za opštu populaciju stariju od 16 godina o unosu natrijuma u količini manjoj od 2 g dnevno (manje od 5 g soli) sa ciljem redukcije vrednosti krvnog pritiska, rizika za KVB, moždani udar i koronarnu bolest. Za populaciju dece uzrasta do 16 godina, date su preporuke o smanjenom unosu soli sa ciljem kontrole krvnog pritiska.…”
Section: Hipertenzija I Unos Soliunclassified
“…Izvesan broj stručnjaka je stava da su efekti smanjenja unosa soli suviše nekonzistentni i generalno isuviše mali da bi to uticalo na formiranje mandatne politike na nacionalnom nivou (111,264), odnosno da efekti redukcije unosa čak mogu biti i nepovoljni (101-102, 265,). Međutim, brojne studije pokazuju da i pored diskretnih efekata na normotenzivne i nešto većeg efekta na hipertenzivne osobe, populacione strategije ostvaruju značajne efekte u smislu smanjenja vrednosti krvnog pritiska, posledičnih KVB, CVB i ostalih HNB.…”
Section: Značaj Istraživanjaunclassified